2006
DOI: 10.1111/j.1600-0714.2006.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyomatous (mesenchymal) hamartoma of the tongue: report of a case

Abstract: A 12-year-old girl presented with three yellowish polypoid lesions in the lateral border of tongue since birth. Histological examination showed oral mucosa covered by squamous epithelium and an underlying vascularized fibrous stroma, containing small and short bundles of striated muscle, corresponding to a rhabdomyomatous hamartoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 4 publications
(6 reference statements)
1
24
0
1
Order By: Relevance
“…In the present case, the lesion showed an unusual presentation; besides mimicking a typical congenital haemangioma, it had predominantly an oral involvement, which is an exceedingly rare location, there being only 3 cases on the oral mucosa reported in the literature [2, 4, 5]. …”
Section: Discussionmentioning
confidence: 58%
“…In the present case, the lesion showed an unusual presentation; besides mimicking a typical congenital haemangioma, it had predominantly an oral involvement, which is an exceedingly rare location, there being only 3 cases on the oral mucosa reported in the literature [2, 4, 5]. …”
Section: Discussionmentioning
confidence: 58%
“…In most cases, the lesion is in the head and neck region. However, it may be found in other body parts and even in regions with no association with skin including the tongue and orbita (7,8). When we screened the literature, we found that no case of hamartoma arising from the hypopharyngeal region has been reported in our country and only a few cases have been reported in the world (5,9).…”
Section: Discussionmentioning
confidence: 95%
“…It can also be associated with congenital abnormalities such as Delleman’s syndrome. RMH very rarely presents intraorally on the tongue with isolated cases reported in the literature 1 2. Reoccurrence of RMH in the oral cavity is very rare.…”
Section: Discussionmentioning
confidence: 99%